PECULIARITIES OF PROFESSIONAL ACTIVITY AND FAMILY RELATIONS OF EMPLOYEES OF THE INTERNAL AFFAIRS BODIES OF THE REPUBLIC OF UZBEKISTAN - Tashtemirovich, Shamshimetov Ruslan (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to analyze the process of professional development of the individual within the framework of social conditions, professional activity, and personal growth, emphasizing the acmeological dimensions of professionalism formation. Method: Using a theoretical-descriptive approach, the study synthesizes perspectives from developmental psychology and acmeology to examine how professional crises, stress, and social environments influence personal and professional evolution. Results: The analysis reveals that professional development involves both constructive and destructive phases shaped by crisis periods, which can either foster personal growth or lead to professional deformation. These crises significantly affect interpersonal and family relationships, while constructive resolution through self-reflection, self-development, and self-improvement enhances professional maturity. Novelty: This article contributes to the field of acmeology by highlighting the dialectical relationship between professional crises and personal growth, offering new insights into how individuals can transform professional challenges into opportunities for self-actualization and sustainable development.